Induction of resistance in cucumber plants against root-rot and damping off diseases using different chemicals - Gobran, Hanaa A.; Gomaa, A.A.; El-Fishawi, A.A. (2008)
Diseases are one of the most important factors affecting cucumber production especially in greenhouses. Roots of cucumber plants were subjected to fungal diseases specially damping- off and root-rot diseases. This work was directed to study the inducing of resistance in cucumber plants against these fungal diseases using three different chemicals namely: ethephon, acetylsalicylic acid, and phosphate salts. Acetyl Salicylic Acid (ASA) was the most effective inducer causing the highest percentages of healthy survival plant followed by ethephon and potassium phosphate mono-basic (Kb2(BHPOb4(B). Seed soaking technique for all tested chemicals, was more effective than foliar application. Untreated plants recorded the least percentages of healthy survival plants. Activity some enzymes such as peroxidase (PO) and polypbenol oxidase (PPO), also, free and total phenol levels, which played an important role in plant resistance, were also determined. All treatments stimulated po activity, the highest activity was recorded for ASA, followed by Kb2(BHPOb4 (Bthen ethephon. The most effective treatment in increasing ppo activity was, ASA followed by, ethephon and Kb2(BHPOb4(B, respectively. The values of free and total phenol were the highest in ASA treatment followed by Kb2(BHPOb4 (Band ethephon treatments, respectively.s
Includes reference.
Summary in Arabic.
1
Keywords: Cucumbers -- Diseases and pests -- Control; Root rots; Damping-off diseases; Fungal diseases of plants